Motivating innovation in a knowledge economy with tax incentives - Diego d'Andria; Ivan Savin (Friedrich Schiller University Jena, 2015)
In the past decades the role of profit sharing schemes (PSS) as a way to foster innovation in a principal-agent context, and more generally of innovation in economic growth, have been widely acknowledged and studied. However, surprisingly little has been done to analyze the interactions between tax policy, PSS and innovative activity, not least because of severe data limitations. In this study we propose an agent-based model to explore the effects of two distinct tax policies on innovation in a pure knowledge economy: a "patent box" incentive and a tax incentive on compensation earned by agents as PSS. A distinct feature of this paper is that in contrast to the conventional assumption that firms (principals) decide on whether to innovate or not, we propose that this decision is actually taken by their employees (agents). We compare the two tax incentives under several distinct specifications and find that the tax incentive on PSS is more efficient than a "patent box" incentive when the role of capital investments in R&D is negligible. With R&D investments in the form of a capacity constraint, both tax incentives are found to play a role in fostering innovation. In addition we find important effects on the incentives relative efficacy due to labor mobility and due to the ability of firms to benefit from knowledge spillovers.
Keywords: H2; O2; J33; 330; agent-based model; innovation; knowledge economy; profit sharing schemes; tax incentives for R&D